Effects of static magnetic field exposure on hematological and biochemical parameters in rats - Amara,Salem (2006)
The present work was undertaken in order to investigate the effects of static magnetic field (SMF) on growth rates, hematopoiesis, plasmatic proteins levels, glucose concentration, lactate dehydrogenase (LDH) and transaminases activities in male rats. Sub-acute exposure of rats during 5 consecutive days to SMF (1h/day at 128mT) induced an increase of plasma LDH activity (+38%, p<0.05), and glucose concentration (+31%, p<0.05), whereas haematological parameters, protein levels, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities remained unchanged. SMF exposure of rats during 30 consecutive days (1hour/day at 128mT) decreased significantly growth rates by the second week and increased significantly the plasmatic total protein levels (+62%, p<0.05), hemoglobin (+10%, p<0.05), red blood cells (+7%, p<0.05), white blood cells (+17%, p<0.05), and platelet number (+10%, p<0.05). Sub-chronic exposure to SMF increased also LDH (+43%, p<0.05), AST (+ 41%, p<0.05) and ALT activities (+95%, p<0.05). In contrast, the glucose concentration was unaffected. These changes suggested that exposure to SMF had a possible effect on the proliferation of blood cells and enzymes release within blood indicating tissue alterations.